The Running of the bare coupling in SU(N) gauge theories - Chris Allton (2007)
For N>4 there is a first order bulk transition that cleanly separates the strong and weak coupling regimes of SU(N) lattice gauge theories with the plaquette action. We find that in this case the calculated string tension can be readily fitted throughout the weak coupling region by a standard 3-loop perturbative expression modified by lattice spacing corrections of the expected form. While our fits demand the presence of the latter, they are not constraining enough to tell us which of the various bare coupling schemes is a `good' one, in the sense that terms in the beta-function beyond 3-loops are indeed negligible (in the relevant range of scales). To resolve this ambiguity we work in SU(3), using the Schrodinger Functional coupling scheme as a benchmark, and find that the Parisi mean-field improved coupling scheme matches it very well. Using the latter scheme, we have fitted the values of the string tension that have been calculated for SU(3) to SU(8), to obtain Lambda_MSbar/sqrt(sigma) = 0.503(2)(40) + 0.33(3)(3)/N**2, where the first error is statistical and the second is our estimate of the systematic error from all sources.